Computed tomography-based conventional imaging features and texture analysis characteristics of chemotherapy drug-related acute pancreatitis - Li, Quanlin; Liu, Chuanmei; Fan, Zijian; Zhang, Hong; Kai, Zhiguo (Frontiers in Medicine, 2025)
PurposeChemotherapy drug-related acute pancreatitis (CDRAP) is a rare adverse event that poses significant challenges to clinicians. This study aimed to describe plain computed tomography (CT)- and contrast-enhanced computed tomography (CECT)-based conventional imaging features and texture analysis characteristics of CDRAP.MethodsA total of 62 patients with initial clinical and/or biochemical evidence of pancreatitis and 34 patients with normal pancreatic manifestations who underwent CT during chemotherapy were retrospectively included. The diagnosis of CDRAP was established based on clinical, imaging, and biochemical findings. Conventional imaging features, texture analysis characteristics, clinical and biochemical parameters, other complications, chemotherapy drugs, and patient outcomes related to CDRAP were recorded.ResultsA total of 20 (32.26%) patients who were clinically diagnosed with CDRAP had normal pancreatic morphology on CT, while 42 (67.74%) patients presented with changes indicative of acute pancreatitis. The CT findings of 62 CDRAP cases were as follows: diffuse (n = 19) or focal (n = 21) pancreatic enlargement, diffuse (n = 12) or focal (n = 4) heterogeneous enhancement, peripancreatic stranding (n = 20), acute peripancreatic fluid collection (n = 10), and pseudocyst (n = 2). A total of 17 texture features were identified to differentiate CDRAP from normal pancreatic manifestations.ConclusionCDRAP mainly manifested as interstitial edematous pancreatitis with/without normal pancreatic morphology on CT. Imaging texture analysis may serve as a potential biomarker for its detection. By combining conventional imaging features with texture analysis characteristics, there is potential to assist radiologists and clinicians in the identification of CDRAP, thereby improving the quality of life for cancer patients.